Secular Evangelicals: Faith-Based Organizing and Four Modes of Public Religion. (27th November 2019) - Markofski, Wes; Fulton, Brad R; Wood, Richard L
Abstract: We present four modes of public religion—secularist, generalist pluralist, particularist pluralist, and exclusivist—and discuss conditions under which white evangelicals employ these different modes. Ethnographic research on white evangelicals participating in multifaith initiatives in Los Angeles, Portland, Boston, and Atlanta indicates that they prefer the secularist mode that avoids religious expression. In addition, the research indicates that when white evangelicals do participate in multifaith contexts where religious expression is encouraged, they prefer the particularist mode that uses faith-specific language rather than the generalist mode that invokes interfaith language. Quantitative data from a national study of community organizing organizations confirms that white evangelicals are more likely to participate in multifaith initiatives that operate in the secularist rather than a religious mode of public engagement. We anticipate that our analytic typology describing four modes of public religion will be valuable for future studies that examine the public engagement of religious actors.